Communication Management of Long Distance Marriage (LDM) Couples to Resolve Marital Conflicts - Salsa Adiningsih; Ayu Usada Rekaningtias (Universitas Negeri Yogyakarta, 2025)
ABSTRACTThis study aims to examine how communication management is conducted in long-distance marriage (LDM) couples based on the Matouschka Dolls communication management theory by Michael Kaye and to identify the factors that hinder communication management in LDM couples in resolving household conflicts. This research employs a qualitative approach with a descriptive method, using data collection techniques through in-depth interviews and documentation conducted from September to November 2024. The findings reveal that: (1) Communication management in LDM couples at the self layer is demonstrated through routine communication, such as chatting, video calls, voice notes, and phone calls, to recognize and understand each other's desires. (2) Communication management at the interpersonal layer is reflected in routine communication, which is key to maintaining the marital relationship. (3) Communication management at the people in system layer shows that work influences the smoothness of communication between couples. (4) Communication management at the competencelayer is demonstrated through emotional regulation, attitudes, thoughts, and varying conflict resolution strategies for each couple. (5) Factors that hinder communication in LDM couples include distance, work related busyness, and limited signal availability. This research is expected to serve as a reference and source of knowledge in the development of Communication Studies in general, including interpersonal communication, communication psychology, and conflict management studies for further research. Additionally, it aims to provide information and evaluation for couples in Long Distance Marriages.Keywords : Communication Management, Long Distance Marriage, Matouschka Dolls, Domestic Conflict.